2016
DOI: 10.24191/jchs.v1i1.5849
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Teaching Methods in Pharmacology in a Malaysian Medical School

Abstract: Introduction: The study attempts to evaluate the students’ perception of pharmacology as a subject, its usefulness in future practice, teaching methods currently used, and their patterns of learning and preparing for exams. Methods: A structured, self-administered questionnaire was distributed to second year medical students. Results: Of the 125 students who participated, 22.73 % considered pharmacology more important than any other subject. The students found small group sessions most interesting followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Among the topics, chemotherapy had the highest percentage of least useful. Our findings were in agreement with a previous study, in which students perceived cardiovascular topic as the most useful while chemotherapy and central nervous system as the less useful topics (Agarwal & Mohd-Ismail 2016). Similar findings were also reported in another study, in which a higher percentage of students found that cardiovascular drugs are useful in future while general pharmacology and chemotherapy are the least interesting topics (Rani et al 2016).…”
Section: Syllabus Content 20supporting
confidence: 93%
“…Among the topics, chemotherapy had the highest percentage of least useful. Our findings were in agreement with a previous study, in which students perceived cardiovascular topic as the most useful while chemotherapy and central nervous system as the less useful topics (Agarwal & Mohd-Ismail 2016). Similar findings were also reported in another study, in which a higher percentage of students found that cardiovascular drugs are useful in future while general pharmacology and chemotherapy are the least interesting topics (Rani et al 2016).…”
Section: Syllabus Content 20supporting
confidence: 93%